La station de Bergusium et le site des Buissières à Panossas (Isère) : de la toponymie à l’archéologie - Matthieu Poux; Aldo Borlenghi (Gallia)
This article focuses on the Bergusium/Birgusia statio to the east of Vienne, traditionally considered to be the current town of Bourgoin-Jallieu (Isère). The scarcity and widespread dispersion of the remains discovered, as well as issues of toponymic derivation, suggest other localities, the foremost of which is Mount Briançon, several kilometres to the west. Its name is derived from the Celtic berg-/brig-, similar to the theonym Bergusia referred to in an Alesian inscription and related to a tutelary goddess of mining in these mountains. Reinforced by the pattern of names in Transalpine and Cisalpine Gaul, this hypothesis would fit well with Briançon, which represents the region’s main Oolitic iron ore deposit. Backed by its eastern foothills, the site of Buissières in Panossas suggests other archaeological arguments to that effect. Located in a valley overlooking the Velin Plain and Bourbre Valley, it is at the junction of two major roads connecting the settlements of Vienne and Lugdunum to Italy via the Alpine passes. Excavations conducted since 2012 have unearthed a vast monumental complex that included stables, blacksmiths’ workshops, storage areas, kitchens and accommodations. It comprised all the features of a high-capacity roadhouse that could correspond to the Bergusium referred to in the Itineraries or to one of its associated facilities.